A Flexible and Conductive Binder with Strong Adhesion for High Performance Silicon‐Based Lithium‐Ion Battery Anode. Issue 9 (17th February 2020) - Tang, Ruixian; Ma, Lei; Zhang, Yu; Zheng, Xiao; Shi, Yongji; Zeng, Xiangyu; Wang, Xiaoyu; Wei, Liangming
Abstract: Silicon is considered to be one of the most promising anode materials for lithium‐ion batteries due to its high capacity. But the silicon anodes undergo huge volume changes during the charge and discharge process, leading to fast capacity fade of Si anodes. To solve this problem, we design a ternary polymer binder composed of poly (vinyl alcohol), poly(dopamine hydrochloride) and poly(3, 4‐ethylenedioxythiophene):poly(styrene sulfonate) for Si anodes. In this polymer composite binder, polydopamine and poly(vinyl alcohol) exhibit strong adhesion with the silicon particles and the copper foils. Additionally, poly (vinyl alcohol) compounded with poly (dopamine hydrochloride) shows high stretchability up to 243.7 %, which benefits for buffering large volume change of Si anodes during cycling. The conducting poly(3, 4‐ethylenedioxythiophene) : poly (styrene sulfonate) in this binder improves the rate performance. Using this multi‐functional binder, the Si anodes show excellent cycling stability even under high Si mass loading. Abstract : Triple P : A flexible and conductive binder composed of poly(vinyl alcohol), poly(dopamine hydrochloride), and poly(3, 4‐ethylenedioxythiophene) : poly(styrene sulfonate) is developed for high‐performance Si‐based anodes. The binder shows high stretchability and adhesion. It protects the Si anodes from cracking during the charge/discharge process and effectively improves the cycling stability, providing a good choice for application in the high‐capacity Si‐based lithium‐ion batteries.